2009
DOI: 10.1007/s11547-009-0427-1
|View full text |Cite
|
Sign up to set email alerts
|

Small (≤2 cm) atypical hepatic haemangiomas in the non-cirrhotic patient: pattern-based classification scheme for enhancement at triple-phase helical CT

Abstract: Triple-phase helical CT scans can distinguish several types of atypical small HHs. The demonstration of patterns similar to those of typical forms on DP CT is fundamental for the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…In the high-energy trauma the use of US as first line diagnostic is superfluous and damaging and the use of CT without and with i.v.c onstrast material is imperative. In order to reduce the radiation dose, particularly in young people or children, CEUS has an important role in the follow-up of conservatively treated traumatic injuries of the abdominal parenchymatous organs (liver, spleen and kidneys) diagnosed by CT [39,40]. …”
Section: Discussionmentioning
confidence: 99%
“…In the high-energy trauma the use of US as first line diagnostic is superfluous and damaging and the use of CT without and with i.v.c onstrast material is imperative. In order to reduce the radiation dose, particularly in young people or children, CEUS has an important role in the follow-up of conservatively treated traumatic injuries of the abdominal parenchymatous organs (liver, spleen and kidneys) diagnosed by CT [39,40]. …”
Section: Discussionmentioning
confidence: 99%
“…Development of multidetector helical CT (MDCT) ensured that dynamic CT could be used to evaluate the hemodynamics of hepatic masses and that triple‐phase helical CT could be used to rapidly scan the whole abdomen in three phases. In triple‐phase helical CT, a single bolus injection facilitates imaging during the phase of preferential arterial enhancement, that is, the arterial phase, followed by the portal venous phase and delayed phase . In humans, previous studies have shown that triple‐phase helical CT improves the detection of various hepatic masses .…”
Section: Introductionmentioning
confidence: 99%
“…In triple‐phase helical CT, a single bolus injection facilitates imaging during the phase of preferential arterial enhancement, that is, the arterial phase, followed by the portal venous phase and delayed phase . In humans, previous studies have shown that triple‐phase helical CT improves the detection of various hepatic masses . In addition, three‐dimensional (3D) reconstruction of triple‐phase helical CT would be useful for preoperative planning …”
Section: Introductionmentioning
confidence: 99%
“…Acquisition of true nonenhanced images (TNE) could therefore be avoided, thereby reducing radiation dose to the patient. This is particularly important in multiphasic protocols for liver imaging [11,12], especially during follow-up and in young patients.…”
Section: Introductionmentioning
confidence: 99%
“…In tal modo sarebbe possibile evitare l'acquisizione d'immagini pre-contrastografiche reali (PCR) riducendo quindi la dose di radiazioni somministrata al paziente; tale aspetto riveste una particolare importanza nei protocolli di studio multifasici del fegato [11,12], specialmente in corso di follow-up e nei soggetti giovani.…”
Section: Introductionunclassified